West Nile Virus Viremia in Wild Rock Pigeons - Allison, Andrew B. (Centers for Disease Control and Prevention, 2004)
Feral rock pigeons were screened for neutralizing antibodies to West Nile virus (WNV) during late winter/spring and summer of 2002 and 2003. Additionally, virus isolation from serum was attempted from 269 birds collected during peak transmission periods. The observed viremia levels and seroprevalence indicate that this species could be involved in amplifying WNV in urban settings.